The Approach of Tajdid’s Umar bin Abdul Aziz Rah. Through the Institution of al-Mazalim in Dealing with the issues of Deviation and Misappropriation - Hamidi Abdul Ghani; Abdul Azib Hussain; Nurul Akma Mohamed (Rabbanica: Journal of Revealed Knowledge)
The behaviors of deviation, misappropriation, and abuse of power are in direct opposition to the principles and teachings of Islam. Islam strictly prohibits the violation of justice and the betrayal of trust. Nevertheless, instances of deviation, misuse, and abuse of authority by governmental authorities persist. Consequently, the establishment of the al-Mazalim Institution occurred, with its primary objective being to eradicate the vicious actions perpetrated by government officials in power. In the annals of Islamic history, Caliph Umar bin Abdul Aziz Rah. stands out as a renowned figure who successfully eliminated the misconduct exhibited by government officials and reinstated the rights of the populace that had been unlawfully seized. This article aims to provide an overview of Umar bin Abdul Aziz Rah's Tajdid strategy through the al-Mazalim Institution. It will explore how this technique was utilized to enforce justice and prevent individuals from deviating from the government. This research employs a qualitative approach, explicitly using a bibliographic methodology combined with a descriptive content analysis technique. The research data was acquired from scholarly publications and academic books, with a particular emphasis on works about the biographical account of Umar bin Abdul Aziz. The study outcomes demonstrate that Umar bin Abdul Aziz effectively implemented eleven tajdid measures to promote justice and combat governmental corruption among officials. The tajdid method of Umar bin Abdul Aziz should be reproduced by individuals in positions of authority to attain divine favor and promote the nation's welfare.